ANALISIS SUMBER MODAL PADA KOPERASI JASA KEUANGAN SYARIAH KALBAR MADANI PONTIANAK - Rizky, Sri; Parijo, Parijo; Khosmas, F.Y (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThe title of this research is asset analysis of Syariah Kalbar Madani finance union Pontianak. Thepurpose of this study to describe the asset in the Syariah Kalbar Madani finance union Pontianak.The method used in this research is descriptive qualitative with the form of ex post facto research, with the data source there are primary data sources and secondary data sources.Data collection techniques used are (1) direct communication techniques with interview guidance tools to the chairman of Pontianak West Kalimantan Civil Service Islamic Cooperatives, (2) documentary / bibliographical techniques in the form of collecting documents needed to obtain the data needed as research material and supporting tools such as visual documentation tools and voice records. Data analysis techniques in this study are data collection, data reduction, data display, and conslusion drawing and verification.The results of the study show that (1) the primary fund for the 2012-2013 increased by 32.17%; -2014 amounting to 2.53; 2014-2015 of 16.51%; the 2015-2016 amounted to 0.60%, (2) the required financial year 2012-2013 deposit fund increased by 9.24%; 2013-2014 of 4.81; 2014-2015 of 15.05 and 2015-2016 of 3.00%, (3) reserve fund in 2012-2013 increased by 6.51%; 2013-2014 of 12.03%; 2014-2015 of 36.97% and 2015-2016 of -0.28%, (4) asset from other Banks and Financial Institutions for 2012-2013 amounting to 3.42%; the percentage of 2013-2014 decreased by 28.71%, the percentage of the 2014-2015 decreased by 4.51%, and the percentage for the 2015-2016 increased by 1.07%. Therefore the management and members must work together to be more active in advancing the business and prioritizing self-fertilization so that cooperatives can become independent and not depend on other parties.Â Keywords: asset, Syariah Kalbar Madani finance unionÂ